The discovery of high endothelial venules. A historical note - Domenico Ribatti (Translational Research in Anatomy)
Background: Endothelial cells are a heterogeneous population. There are differences between the different species' endothelium, large and small vessels, and between endothelial cells derived from various microvascular endothelial beds. In this context, endothelial cells of high endothelial venules (HEVs) represent an extremely interesting and not-yet completely investigated cell population. Methods: A literature search in PubMed on the history of HEVs was conducted. The keywords used in the search criteria were “High endothelial venules,” “Immunity,” “B lymphocytes,” “T lymphocytes,” and “Lymph nodes.” The results were summarized in a short narrative historical review based on published papers on the role of HEVs in immunity, inflammation, and cancer. Results: HEVs are morphologically characterized by a plump, almost cuboidal appearance, a rounded nucleus, a thicker basement membrane, and a layer of mesenchymal cells outside the basement membrane. HEVs are specialized blood vessels mediating lymphocyte trafficking to lymph nodes and other secondary lymphoid organs. HEVs expand during inflammation in immune-stimulated lymph nodes and are profoundly remodeled in metastatic and tumor-draining lymph nodes. Conclusion: This article emphasizes the important role of HEVs in immunity, inflammation, and cancer. However, although many aspects of HEVs are still to be discovered, their therapeutic modulation already offers interesting results, especially for cancer treatment.